THE The Influence of Planning and Budgeting Policy toward Performance Accountablity of Citengah Village Government, South Sumedang District, Sumedang Regency - Fajar Putradi, Didit; Aceng Ulumudin; Gugun Geusan Akbar; Mulyaningsih (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The Law of the Republic of Indonesia Number 6 of 2014 enabling village governments to manage their resources independently through planning and budgeting policies. However, the implementation of this policy often faces challenges in performance accountability. The Village Government Agency Performance Accountability System (SAKIP Desa) implemented by the Citengah Village Government, South Sumedang District, Sumedang Regency present innovative solution in improving performance accountability of village governments. This study aims to analyze how planning and budgeting policies affect the performance accountability of the Citengah Village Government within the SAKIP Desa framework. The research method used is qualitative approach with data collection techniques carried out through Desk Study on planning and budgeting documents and performance reports of Citengah Village with in-depth interviews and field observations. Data analysis conducted by analyzing the SAKIP Desa achievements of Citengah Village in 2024 and analyzing the influence of planning and budgeting policies toward performance accountability. The results of the study show that Citengah Village has achieved SAKIP Desa score of 80.63 (grade B), which indicates good performance of management system but still requires improvement in several components, such as the implementation of performance measurement, utilization of information and performance evaluation and performance reporting. Planning and budgeting policies based on a logical framework and measurable performance levels, implementation accompanied by action plans and periodic evaluations have proven to have a positive effect on the performance accountability. Based on these findings, this study recommends that the Citengah Village Government improve the unoptimal component in the SAKIP Desa, formulate a more ideal performance tree by strengthening the logical framework of planning and budgeting